Pengaruh Promosi dan Tingkat Rasio Bunga terhadap Keputusan Pengambilan Kredit Pada KSP Chandsra Sedana Asri di Gianyar - Murti, I Wayan Saktya; Wijaya, Putu Yudy; Pratiwi, Komang Ary (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Savings andss loan cooperatives are microfinance institutions that provide capital loans to their members. Savings ands loan cooperatives are often called KSP ands Kospin Jasa. Savings ands loan cooperative products are loans/credit. Customer decisions in taking out credit are often influenced by promotions ands interest rates. The formulations ofs the problem ands objectivess in thiss research is to determinse thes influence of promotions ands interest rates on credit decisions. This research was carried out at KSP Chandsra Sedana Asri withs a sample of 90 respondentss. The datas analysiss techniques useds are the Classic Assumption Test, Multiples Linears Regressions, Determination Coefficient, t Test ands F Test. Baseds on the research results, it casn be seen that promotion has a positive ands partially signifficant effecst on credit decisions at KSP Chandsra Sedana Asri, interests ratess haves a negative ands partially insignificants effects ons credit decisions at KSP Chandsra Sedana Asri, promotions ands interesst rates have a partial effecst. Simultaneous decision making credit at KSP Chandsra Sedana Asri. The magnitudes of the influences of the independents variable on repurchasse interest is 36.9% .